Strategic Analysis To Improve The Development Of Zis Lazismu Funds To Improve The Prosperity Of Marginal Communities In Denpasar City - Alwiyah Alwiyah; Iwan Setiadi (International Journal of Economics, Business and Innovation Research, 2024)
The Denpasar City Zakat Amil Institution is used as a means of providing capital assistance to someone who is entitled to receive zakat in order to meet the needs of the person or help develop a business that will be created by the person. However, there are many things that are missed so that the planning of the Institution is not as it should be and then can harm all parties because the system has not been clear handling. This study intends to analyze how to develop zakat through Lazismu with several new ways so as to know the differences between the previous and current methods of the institution and to know what is the effective model for using zakat implemented in LAZISMU, then the empowerment model is also implemented mustahik For know How many income mustahik after receive zakat production funds so that experience improvement or change from aspect income , ethics business . and the affordability of ZIS LAZISMU in utilize zakat wisely effective through the program. In this study, the method used is quantitative research by collecting several data based on references from several trusted journals , several annual reports provided by the Lazismu Institute directly to distribution hardcopy and softcopy questionnaires . Research results on ZIS Lazismu state that the strategy for developing old and new programs For in the future Can make Lazismu For help more Lots for the community in the city of Denpasar through its programs .